Air pollutants and SARS-CoV-2 in 33 European countries. - Lembo, Rosalba; Landoni, Giovanni; Cianfanelli, Lorenzo; Frontera, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: A potential correlation between severe acute respiratory syndrome coronavirus 2 and air pollution has been suggested in some nationwide studies. It is not clear whether air pollution contributes to the spread of SARS-CoV-2 and to increase mortality.Methods: Data on COVID-19 incidence, mortality rate, air pollution, and greenhouse gas element of 33 European countries were extracted from public available databases and analysed with Pearson correlation analysis for the overall population and normalizing for the population over 65 years.Results: Air pollutant agents such as particulate matter